2003
DOI: 10.1242/dev.00428
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid-induced developmental defects are mediated by RARβ/RXR heterodimers in the pharyngeal endoderm

Abstract: Fusion and hypoplasia of the first two branchial arches, a defect typically observed in retinoic acid (RA) embryopathy, is generated in cultured mouse embryos upon treatment with BMS453, a synthetic compound that exhibits retinoic acid receptor β (RARβ) agonistic properties in transfected cells. By contrast, no branchial arch defects are observed following treatment with synthetic retinoids that exhibit RARα or RARγ agonistic properties. The BMS453-induced branchial arch defects are mediated through RAR activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 78 publications
3
81
0
Order By: Relevance
“…Conversely, ectopic RA (or RAR agonists) has significant effects on the anterior ectodermal development, including on anterior endodermalectodermal contacts (e.g., Lee et al, 1995;Kuratani et al, 1998;Escriva et al, 2002;Matt et al, 2003). Matt et al (2003) showed that by using a RAR␤ specific agonist the BA defects associated with RA tetratogenesis were largely replicated; they also applied the agonist to mice carrying a RA-responsive element (RARE) that normally gives expression only up to the second pharyngeal pouch and found reporter expression throughout the APE.…”
Section: Legacy For the Anterior Pahryngeal Endodermmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, ectopic RA (or RAR agonists) has significant effects on the anterior ectodermal development, including on anterior endodermalectodermal contacts (e.g., Lee et al, 1995;Kuratani et al, 1998;Escriva et al, 2002;Matt et al, 2003). Matt et al (2003) showed that by using a RAR␤ specific agonist the BA defects associated with RA tetratogenesis were largely replicated; they also applied the agonist to mice carrying a RA-responsive element (RARE) that normally gives expression only up to the second pharyngeal pouch and found reporter expression throughout the APE.…”
Section: Legacy For the Anterior Pahryngeal Endodermmentioning
confidence: 99%
“…Matt et al (2003) showed that by using a RAR␤ specific agonist the BA defects associated with RA tetratogenesis were largely replicated; they also applied the agonist to mice carrying a RA-responsive element (RARE) that normally gives expression only up to the second pharyngeal pouch and found reporter expression throughout the APE. Thus, the lack of proper anterior endodermal-ectodermal contacts and development were correlated with abnormal, anterior RA signaling.…”
Section: Legacy For the Anterior Pahryngeal Endodermmentioning
confidence: 99%
“…The rationale for these studies is that most, if not all, tissues express at least one of the RARs (Dolle, 2009 for a review), that should activate the reporter upon binding of endogenous RA. The RARE-hsp68-lacZ transgene has been widely used in subsequent studies (e.g., Malpel et al, 2000;Mic et al, 2002;Niederreither et al, 2002b;Fan et al, 2003;Matt et al, 2003Matt et al, , 2005Yashiro et al, 2004;Sirbu et al, 2005;Molotkov et al, 2006;Sirbu and Duester, 2006;Ribes et al, 2009;Zhao et al, 2009). Three lines of evidence have validated this transgene as a reliable indicator of RA activity: (1) there is a close match between the patterns of lacZ activity and the expression patterns of RA-synthesizing enzymes (Rdh10, Raldhs) at early embryonic stages, (2) activity of the lacZ reporter is severely down-regulated in knockout mice for the above enzymes (Niederreither et al, 1999;Mic et al, 2002;Matt et al, 2005;Molotkov et al, 2006;Sandell et al, 2007), (3) on the other hand, the reporter is almost ubiquitously activated within 6 h after administration of a bolus dose of RA to the pregnant mothers (Rossant et al, 1991), and is ectopically activated when RA-metabolizing enzymes are absent Sakai et al, 2001;Uehara et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental manipulation of retinoid receptor signaling also produces phenocopies of DGS; compound inactivation of RA receptors RAR␣ and RAR␤ (Lohnes et al, 1994;Mendelsohn et al, 1994;Ghyselinck et al, 1998;Dupe et al, 1999), retinoid X receptor RXR␣ and RARs ␣, ␤, and ␥ (Kastner et al, 1997), and chemical alteration with a either a pan-RAR antagonist (Wendling et al, 2000) or an RAR␤ agonist (Matt et al, 2003) all display phenotypes where development of the pharyngeal region is disrupted.…”
Section: Introductionmentioning
confidence: 99%